Motif Perempuan Memposting Konten Bentuk Tubuh Ideal Di Instagram : Studi Kasus Pengguna G Sports Center - Riani Zahra; Dion Eriend (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to describe and analyze the motives of female users of G Sport Center in posting ideal body shape content on Instagram. Using a qualitative case study approach, data were obtained through in-depth interviews, observation, and documentation of the activities of five main informants and one supporting informant. The findings show that their main motivations include self-expression, documentation of physical development, personal branding, and the hope of gaining support and recognition from the digital fitness community. Instagram serves as a documentation medium as well as a space for social interaction through the Reels and Stories features. Some informants faced psychological challenges in the form of insecurity due to social comparison and the use of filters. This study emphasizes the dual role of Instagram as a source of motivation as well as a trigger for social pressure, and as a medium for identity formation in the digital era. Recommendations are given to strengthen digital literacy and community support to create inclusive and healthy spaces for expression on social media and in the fitness world.